2018
DOI: 10.1021/acscatal.7b03464
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrochemical Hydrogen Peroxide Production from Molecular Oxygen on Nitrogen-Doped Mesoporous Carbon Catalysts

Abstract: Electrochemical hydrogen peroxide (H 2 O 2 ) production by two-electron oxygen reduction is a promising alternative process to the established industrial anthraquinone process. Current challenges relate to finding cost-effective electrocatalysts with high electrocatalytic activity, stability, and product selectivity. Here, we explore the electrocatalytic activity and selectivity toward H 2 O 2 production of a number of distinct nitrogen-doped mesoporous carbon catalysts and report a previously unachieved H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
271
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(291 citation statements)
references
References 53 publications
9
271
1
Order By: Relevance
“…Hence, the increased mesoporosity and the largerp ores are correlated with an increased selectivity towards H 2 O 2 under the appliedc onditions. These findings are in agreement with past [17] and recent reports, [18] which correlate extensive mesoporosityo ft he carbon catalystw ith high H 2 O 2 selectivity.T he high surface area is also correlated with high activity as previously demonstrated. [19] Electrochemical impedance spectroscopy (EIS) characterization of the ORR process in at hree-electrode configuration was performed with an optimized Nafion-containing (5 mL) thin-film catalysta nd is discussed in the SupportingI nformation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the increased mesoporosity and the largerp ores are correlated with an increased selectivity towards H 2 O 2 under the appliedc onditions. These findings are in agreement with past [17] and recent reports, [18] which correlate extensive mesoporosityo ft he carbon catalystw ith high H 2 O 2 selectivity.T he high surface area is also correlated with high activity as previously demonstrated. [19] Electrochemical impedance spectroscopy (EIS) characterization of the ORR process in at hree-electrode configuration was performed with an optimized Nafion-containing (5 mL) thin-film catalysta nd is discussed in the SupportingI nformation.…”
Section: Resultssupporting
confidence: 93%
“…Hence, the increased mesoporosity and the larger pores are correlated with an increased selectivity towards H 2 O 2 under the applied conditions. These findings are in agreement with past and recent reports, which correlate extensive mesoporosity of the carbon catalyst with high H 2 O 2 selectivity. The high surface area is also correlated with high activity as previously demonstrated …”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have elucidated the importance of surface charges and surface defects in determining the performance of carbon‐based catalysts. Furthermore, the porosity (pore size and pore density) of the carbon material is also observed to largely influence the mass transport while providing additional active sites toward H 2 O 2 production …”
Section: H2o2 Production Over Nonmetal‐based Electrocatalystsmentioning
confidence: 99%
“…Sun et al observed that carbon catalysts exhibiting a high selectivity for H 2 O 2 possessed a positive zeta potential, an indication of the amount of surface charges. This observation may have two possible explanations.…”
Section: H2o2 Production Over Nonmetal‐based Electrocatalystsmentioning
confidence: 99%
“…) could be a viable solution. Using renewable electricity as the energy source, electrochemical and photoelectrochemical conversion schemes can perform chemical reactions under ambient conditions (room temperature and atmospheric pressure) and have been utilized to synthesize many valuable chemicals including hydrogen, hydrogen peroxide, hydrocarbons, and oxygenates . In an ideal scenario, as a good source of hydrogen, NH 3 can combine with oxygen (O 2 ) in the fuel cell system to generate electricity and N 2 ; while in the other half of the cycle, N 2 can be electrochemically transformed into NH 3 when coupled with a renewable electricity source, establishing a nitrogen‐neutral cycle for renewable energy utilization and regeneration as presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%